TRANSFORMASI PEMBELAJARAN SASTRA MELALUI MODEL DEEP LEARNING DAN PROBLEM-BASED LEARNING BERBANTUAN PLATFORM DIGITAL DI SMK DISTRIK AILEU - Baptista Mendoca; Amril Amir; Diky Saputra Hutabalian; Iwan Sugiyanto; Fransiska Marta Sari; Shafiyyah Ambarah; Hilda Hanifah (Balai Bahasa Provinsi Bali, 2026)
This study aims to analyze the transformation of literature learning through the implementation of Deep Learning and Problem-Based Learning (PBL) models integrated with digital platforms among vocational high school students in the Aileu District, Timor-Leste. The development of educational technology opens opportunities for literature learning that no longer focuses on memorization but rather on deep understanding. The deep learning approach is used to encourage analysis, reflection, and critical interpretation of literary texts, while PBL presents authentic problem-based learning through collaboration and active discussion. This study employs a quasi-experimental method with two groups, namely an experimental class that applies Deep Learning–PBL assisted by digital platforms and a control class using conventional methods. The research instruments include a literary comprehension test, student participation observation sheets, and a questionnaire on perceptions of technology utilization. The results show a significant improvement in literary analysis skills, learning engagement, and interpretive creativity of students in the experimental class compared to the control class (p < 0.05), with moderate to high effect sizes. The use of digital platforms also strengthens the learning experience through multimedia, online collaboration, and rapid feedback. This study concludes that the integration of deep learning, PBL, and digital technology is effective in transforming literature learning into a more profound, interactive, and relevant practice for 21st-century education